Ochrobactrum anthropi bacteremia with variable clinical course: report of two cases - Arimuthu, Durga Arinandini; Lim, Christopher Thiam Seong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Ochrobactrum anthropi is a rare nosocomial pathogen that is manifesting itself mostly in immunocompromised patients and those with indwelling catheters. Identification of the microorganism is challenging and the ability to survive in aquatic surroundings have made it a clinically significant pathogen. Furthermore, the clinical picture of O. anthropi infection, is not well described. It may manifest in any form of clinical infections though bacteremia is the most common mode of presentation reported in the limited literature. We report here two cases of O. anthropi bacteremia presenting in an immunocompetent and an immunocompromised host respectively with different clinical manifestation and response. In view of the highly variable presentation of O.anthropi, a high index of suspicion must be given to at risks patients to ensure the timely diagnosis and optimal clinical outcome.